O olho que tudo vê: a vigilância dos Estados Unidos sobre o Brasil 1946-1964 - Tobias, Fabio Lucio Mello (2008)
The goal of this dissertation is to demonstrate the observation and surveillance of the United States over the Brazilian politics by the CIA from 1947 to 1964. Therefore, based on studies about the subject and with access to declassified documents of the period as secret and released by the U.S. government sought also show that the alignment of Brazil Foreign Policy United States was vital to the interests of the hegemonic power in the continent during the early-Cold War